2015
DOI: 10.1051/0004-6361/201425209
|View full text |Cite
|
Sign up to set email alerts
|

SuzakuX-ray study of the double radio relic galaxy cluster CIZA J2242.8+5301

Abstract: Context. We present the results from Suzaku observations of the merging cluster of galaxies CIZA J2242.8+5301 at z = 0.192. Aims. To study the physics of gas heating and particle acceleration in cluster mergers, we investigated the X-ray emission from CIZA J2242.8+5301, which hosts two giant radio relics in the northern and southern part of the cluster. Methods. We analyzed data from three-pointed Suzaku observations of CIZA J2242.8+5301 to derive the temperature distribution in four different directions. Resu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
105
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(126 citation statements)
references
References 76 publications
19
105
2
Order By: Relevance
“…The hard X-ray flux from inverse Compton scattering is larger than the synchrotron flux, because the magnetic field of B d = 0.30 µG is smaller than BCMB ≈ 3.24(1 + z) 2 µG ≈ 4.6 µG, at which synchrotron cooling is comparable to the cooling by inverse Compton scattering. 1 We analyze the Suzaku data of the Sausage Cluster (see Akamatsu et al 2015) and find that the upper limit of the nonthermal emission is 8.2×10 −13 erg s −1 in the 0.3-10 keV band, which is consistent with our prediction in figure 3b.…”
Section: Resultssupporting
confidence: 84%
“…The hard X-ray flux from inverse Compton scattering is larger than the synchrotron flux, because the magnetic field of B d = 0.30 µG is smaller than BCMB ≈ 3.24(1 + z) 2 µG ≈ 4.6 µG, at which synchrotron cooling is comparable to the cooling by inverse Compton scattering. 1 We analyze the Suzaku data of the Sausage Cluster (see Akamatsu et al 2015) and find that the upper limit of the nonthermal emission is 8.2×10 −13 erg s −1 in the 0.3-10 keV band, which is consistent with our prediction in figure 3b.…”
Section: Resultssupporting
confidence: 84%
“…′ 4, respectively. Interestingly, the distance ratio is approximately equal to the ratio of the Mach numbers estimated by X-ray temperature, (Akamatsu et al 2015), where M NR = 2.7 Since the distance is equivalent to the merger timescale multiplied by the velocity, those positions relative to the center of mass are simply explained by the timescale after the core passage. In other words, the formation of radio relic is possibly triggered after the core passage.…”
Section: Discussionmentioning
confidence: 99%
“…Brunetti & Jones 2014) and the spectral aging (van Weeren et al 2010) suggest that radio relics are connected with merger shocks. Indeed, X-ray observations (Akamatsu & Kawahara 2013;Akamatsu et al 2015) discovered the temperature jump around the radio relics, though the Mach numbers estimated by X-ray observation (M NR = 2.7 ± 0.5 and M SR = 1.7 ± 0.3). are somewhat lower than those (M NR = 4.58 ± 1.09 and M SR = 2.81 ± 0.19) by radio spectral index based on DSA model [Vol.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vazza & Brüggen (2014) andVazza et al (2015 show that the observed γ-rayupper limits are in tension with the relative acceleration efficiency of electrons and protons that is expected from DSA. Tension with DSA has also been found from the discrepancy between the measured Mach numbers from X-ray observations and the radio spectral index (see Equation (3)) for some relics (e.g., Akamatsu et al 2015;Itahana et al 2015;van Weeren et al 2016a).…”
Section: Acceleration Mechanismsmentioning
confidence: 99%